Геополитика китайско-белорусского экономического сотрудничества - Дубонос, И. И. (БНТУ, 2015)
This paper offers new approach to the understanding of geopolitical component of Sino-Belarusian economic cooperation. Author states that so-called Northern Branch of the Silk Road Economic Belt is dedicated not to the creation of alternative transport corridor between Europe and People’s Republic of China, but to the economic colonization of post-Soviet states. Belarus, due to its stable political regime and valuable geographical position, is becoming the main hub for Chinese trade goods, which should compete on markets of European Russia. The main conclusion is the following: Belarus should strive to deepen its connection with China, because our state is the main beneficiary of Chinese presence in core Eurasia.